HUBUNGAN KUALITAS SANITASI RUMAH DENGAN KEJADIAN PENYAKIT INFEKSI SALURAN PERNAPASAN AKUT (ISPA) DI WILAYAH KERJA PUSKESMAS IV DENPASAR SELATAN KOTA DENPASAR - I Gede Sumertha Gapar; Nyoman Adiputra; I.B.G. Pujaastawa (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2015)
Besides positive results, the rapid development and growth of Denpasar City has also brought some problems to the Government of Denpasar City, for example the emergence of housing complexes that did not meet health standards and requirements. This problem can cause negative impacts toward the health condition of city residents, especially in the form of diseases influenced by environment factors such as acute respiratory infections (ARI). Based on that phenomena this study was carried out to examine the causal relationship between home sanitation factors (ventilation, natural lighting, humidity, temperature, population density, and air pollution) and the event of acute respiratory infections (ARI) in the working area of Public Health Centre IV of Denpasar Selatan District, in Denpasar City. This study had an observational nature and employed a cross-sectional design. Based on data analysis applied, this study belong to analytical studies. Population size of this study was 5,777 and covered all inhabited houses in the working areas of Public Health Centre IV of Denpasar Selatan District. Sample of 97 houses were taken using proporsional stratified random sampling. Statistical tests shows that: (1) the quality of house sanitation has a significance value p = 0.000 (sig p <0.05), (2) house ventilation has a significance value = 0.162 (sig p>0.05, (3) natural lighting has a significance value p=0.002 (sig p<0.05), (4) Room humidity has a significance value p=0.003 (sig p<0.05), (5) Room temperature has a significance value p=0.491 (sig p>0.05), (6) house population density has a significance value p=0.123 (sig p>0.05), (7) Air population in the house has a significance value p=0.001(sig p<0.05). Based on the results of our study it can be concluded that the quality of house sanitation affect the event of acute respiratory infections (ARI) diseases. The variables of house sanitation that affect the event of ARI diseases are: room humidity (OR=0.321), air population in the house (OR= 0.233), natural lighting (OR= 0.151). Our study found that the probability of people who live in a house with below-standard-sanitationquality to be stricken by ARI diseases was 97.7%. Based on the results of our study it can be suggested that to the people that built the house of a qualified health.